2021
DOI: 10.3389/fimmu.2020.588227
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Resident Memory γδT Cells in Murine Uterus Expressed High Levels of IL-17 Promoting the Invasion of Trophocytes

Abstract: γδT cells are non-conventional T cells and serve as the bridge for connecting the innate and adaptive immune systems. γδT cells form a substantial population at barrier sites and play an important role in the development of physiology, inflammation, autoimmune diseases and tumors. γδT cells not only distribute in the maternal-fetal interface during pregnancy but also in non-pregnant uterus. However, the phenotypes and functions of γδT cells in uterus were not clear. In the current study, we found that the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Our previous work showed that γδT cells were enriched in uterus and highly expressed IL-17. 20 In the present study, we found that estrogen could increase the production of IL-17 in uterus after stimulation with anti-CD3 in vitro. During polyclonal activation, γδT cells in uterus expressed high levels of IL-17 but the expression of IFN-γ was much scarcer.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our previous work showed that γδT cells were enriched in uterus and highly expressed IL-17. 20 In the present study, we found that estrogen could increase the production of IL-17 in uterus after stimulation with anti-CD3 in vitro. During polyclonal activation, γδT cells in uterus expressed high levels of IL-17 but the expression of IFN-γ was much scarcer.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, uterine γδT cells produced high levels of IL-17 that were the main source of IL-17 in uterus to promote the invasion of trophocytes in vitro. 20 Our current study showed that subcutaneous injection of mice with estrogen could recruit γδT cells to uterus by CXCR3-CXCL10 chemokine axis. In addition, we found that estrogen enhanced the production of IL-17 by promoting the expression of transcription factor IRF-4 at mRNA and protein levels but not RORγt and STAT3.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the mesenteric lymph nodes of mice infected with Listeria, Vγ4 + and Vγ6 + γδT17 cells can rapidly proliferate in response to that pathogen in a TCR-dependent manner [64]. Similar memory-like γδT17 cell responses have also been observed in mouse models of psoriasis dermatitis and Staphylococcus aureus infection [65]. Of course, this phenomenon may be due to an increased frequency of γδT17 cells, resulting in activity accumulation.…”
Section: Immune Memory Effect Of γδ T Cellsmentioning
confidence: 75%
“…56 Cell populations bearing tissue-resident memory T cell markers (CD69 + CD103 + ) also increased. Because these T cells were CD4 − CD8 − we speculate they could be γδ T cells, a subset of T cells enriched in epithelial and mucosal tissues that are activated in an MHC-independent manner 57,58 . Unexpectedly, in post-booster BAL fluid and sera, antigen-specific IgG and IgA were present following intranasal vaccination with MPLA NPs plus S-S, but not with PUUC NPs or MPLA+PUUC NPs.…”
Section: Discussionmentioning
confidence: 99%